In the mirror of Persian kings: the origins of Perso-Islamic courts and empires in India - Auer, Blain (Cambridge, UK; New York, USA: Cambridge University Press, 2021)
"For a period of nearly eight hundred years, Perso-Islamic kingship was the source for the dominant social and cultural paradigms organizing Indian political life. In the medieval world of South Asia, Persian kingship took the form of a hybridized and adaptive political expression. The Persian king embodied the values of justice, military heroics, and honor, ideals valorized historically and transculturally, yet the influence of the pre- Islamic Persian past and Persian forms of kingship has not yet been fully recognized. In this book, Blain Auer demonstrates how Persian kingship was a transcultural phenomenon. Describing the contributions made by kings, poets, historians, political and moral philosophers, he reveals how and why the image of the Persian king played such a prominent role in the political history of Islamicate societies, in general, and in India, in particular. By tracing the historical thread of this influence from Samanid, Ghaznavid, and Ghurid Empires, Auer demonstrates how that legacy had an impact on the establishment of Delhi as a capital of Muslim rulers who made claims to a broad symbolic and ideological inheritance from the Persian kings of legend"--
The History of Persian Kingship and Persianization in South Asia -- Kings in History: Persian Royal Genealogies and Muslim Rulers -- Warrior King: Slaying Demons, Hunting Beasts, and War -- Theory and Application of Persianate Political Ethics in India -- The Pen, the Sword, and the Vizier.
Includes bibliographical references and index.
Keywords: Samanid dynasty, -- 9th-10th centuries; Sultans -- India -- History; Ghaznevids -- India -- History; Ghurids -- History; Islamic civilization -- Iranian influences; India -- Politics and government -- 997-1765.; Southeast Asia -- Kings and rulers